An empirical study on the teaching mode of cultural translation in college English based on the Production Oriented Approach (POA). - Tong He; Chongyue Li (PLoS ONE, 2025)
Under the circumstances of "Curriculum ideological and political", in order to adapt to the reform of college English teaching and the needs of Education for Sustainable Development (ESD), as well as optimize the A-level distinguishable teaching mode of college English stratified teaching, this paper takes the fifth stage of "Production Oriented Approach" (POA) as the theoretical basis and completes a one-semester mixed teaching experiment for the Chinese culture translation section in New Horizon College English. Taking the paragraph translation of "Tai Chi" as an example, a detailed teaching design and implementation process were presented, attempting to construct a sustainable blended teaching model for the cultural translation section of college English. Quantitative and qualitative data statistics and analysis were used to evaluate and reflect on the effectiveness of teaching practice. The research results indicate that compared to traditional college English teaching, blended teaching model based on POA can enhance the English language and cultural output ability of A-level students. The mode is of sustainable value, which is beneficial to students understanding of Chinese culture, thereby enhancing their cultural confidence. In addition, this model can effectively enhance teachers' ability to apply theoretical knowledge in blended teaching design, which has certain significance for the college English curriculum reform and the practice of "curriculum-based political and ideological education".